(untitled) (Journal of Medical & Health Sciences Review, 2025)
Aim: This study examined the influence of family presence during pediatric emergency resuscitation on parental anxiety and nurse performance in a tertiary care hospital setting. Methods: This study utilized an analytical, cross-sectional, and pretest-posttest design to evaluate the impact of family presence on the anxiety levels of parents and the performance of nurses during emergency resuscitation procedures in a pediatric emergency department.The investigation was carried out in the Pediatric Emergency Department of Nishtar Hospital, Multan, between September 1 and December 30, 2024. The study population consisted of all nurses (N = 150) working in the pediatric unit. The sample consisted of 120 nurses who met the inclusion criteria and provided consent. Data were collected using a demographic information form, the State-Trait Anxiety Inventory (STAI) for nurses and parents, and a Nurse Performance Checklist. Participants first completed the information form and the Trait Anxiety Inventory. The research was conducted in two phases with the same nurse sample. In the first phase (Family Presence), nurses performed resuscitation with a family member present in a designated area, after which they and the accompanying parent immediately completed the State Anxiety Inventory. Nurse performance was simultaneously rated by an independent observer. In the second phase (Standard Care), after a 15-day interval, the same nurses performed resuscitations without family presence,and the same post-procedureassessments were conducted. Result and Conclusion: The mean trait anxiety score for nurses was at a moderate level. A statistically significant increase (p<0.001) in nurses’ state anxiety was observed during resuscitation with family presence compared to those without. Conversely, parental anxiety was significantly lower when they were present. Nurse performance scores showed no significant difference between the two groups. Despite increased personal anxiety, supporting family presence during pediatric resuscitation is recommended due to its benefits for parents. Continuous training in family-centered care and communication strategies is essential for emergency nursing staff.